Colonic metastasis of a huge soft uterine leiomyoma in a postmenopausal woman: a case report - Tang, JianXin; Xu, RuiBo; Xi, XiaoYu; Liu, Ying; Hao, ZengFang; Du, JieXian; Du, XiaoLi (Frontiers in Oncology, 2025)
Background.Uterine leiomyomas are the most common benign tumors of the female reproductive system, arising from the overgrowth of smooth muscle tissue within the uterus. Typically, they present as solid, spherical masses that are firmer than the surrounding uterine muscle layer. Onset generally occurs between the ages of 30 and 50, with these tumors often located in the uterine body or cervix. Some women may experience gradual tumor enlargement, accompanied by symptoms such as vaginal bleeding, lower abdominal pain, frequent urination, and constipation. In such instances, surgical treatment should be considered the first choice.Case summaryIn this case, A 59-year-old woman presented with a large, soft, and irregularly shaped uterine leiomyoma, formed by the fusion of hundreds of smaller fibroids, which had metastasized to the sigmoid colon.Immunohistochemical analysis further demonstrated that benign uterine leiomyomas may present with morphological features, consistency, and an invasive growth pattern akin to malignant tumors.InnovationsUterine leiomyomas are benign tumors that rarely metastasize; however, case reports have documented instances of distant metastasis.ConclusionThe purpose of this study is to report a case of a uterine leiomyoma with intestinal metastasis, analyze its rare characteristics and invasive growth pattern, and enhance the understanding of this tumor.